Surgical effect of the medial wall resection of the cavernous sinus for functional pituitary adenomas - Liang, Xiao; Li, Zhuoqun; Xing, Mengyang; Gao, Wenbo; Liu, Pengfei (Frontiers in Surgery, 2024)
BackgroundThe surgical treatment of pituitary adenomas (PAs) is aimed at achieving maximal tumor resection, relieving the compression, and correcting the disorders of pituitary hormones. Parasellar dural invasion is a primary factor in the failure of the surgery. By comparing the two operations of tumor excision combined with resection of the medial wall of the cavernous sinus (MW) and simple tumor excision, we further confirmed the clinical effectiveness and safety of the resection technique of the MW.Methods41 patients with functional pituitary adenoma (FPA) were divided into two groups according to the operation. The experimental group consisted of 20 patients who underwent tumor excision combined with resection of the MW via endonasal transsphenoidal approach and 21 patients who underwent simple pituitary tumor excision as the control group. Both groups were followed up for 12 months and matched for age, sex, BMI, tumor type, Knosp grade, maximum tumor diameter, hypertension, diabetes, and coronary disease. Perioperative-related indicators, biochemical remission rates, tumor recurrence rates, and complications were assessed.ResultsA total of 21 medial walls were removed in 20 patients, 15 (71%) specimens had pathologically confirmed tumor invasion. Biochemical remission rates and average operative duration in the experimental group were more than in the control group (P < 0.05). The remaining perioperative indicators, complications, and tumor recurrence rates had no statistically significant difference (P > 0.05).ConclusionThe technique of the MW removal via endonasal transsphenoidal approach for FPAs is safe and effective, with a high biochemical remission. The average operative duration for MW removal may be longer than that for simple tumor excision.